Clinical courses and complications of young adults with Autosomal Recessive Polycystic Kidney Disease (ARPKD) - Burgmaier, Kathrin; Kilian, Samuel; Schäfer, Susanne; Wühl, Elke; Schaefer, Franz (Scientific reports, 2019)
Autosomal recessive polycystic kidney disease (ARPKD) is a severe pediatric hepatorenal disorder with pronounced phenotypic variability. A substantial number of patients with early diagnosis reaches adulthood and some patients are not diagnosed until adulthood. Yet, clinical knowledge about adult ARPKD patients is scarce. Here, we describe forty-nine patients with longitudinal follow-up into young adulthood that were identified in the international ARPKD cohort study ARegPKD. Forty-five patients were evaluated in a cross-sectional analysis at a mean age of 21.4 (±3.3) years describing hepatorenal findings. Renal function of native kidneys was within CKD stages 1 to 3 in more than 50% of the patients. Symptoms of hepatic involvement were frequently detected. Fourteen (31%) patients had undergone kidney transplantation and six patients (13%) had undergone liver transplantation or combined liver and kidney transplantation prior to the visit revealing a wide variability of clinical courses. Hepatorenal involvement and preceding complications in other organs were also evaluated in a time-to-event analysis. In summary, we characterize the broad clinical spectrum of young adult ARPKD patients. Importantly, many patients have a stable renal and hepatic situation in young adulthood. ARPKD should also be considered as a differential diagnosis in young adults with fibrocystic hepatorenal disease.